An experimental study on performance enhancement of a PCM based solar-assisted air source heat pump system under cooling modes. (5th May 2016) - Ni, Long; Qv, Dehu; Yao, Yang; Niu, Fuxin; Hu, Wenju
Highlights: A PCM based solar-assisted air source heat pump system is proposed. Performance of the system in cooling/heating mode is improved substantially. Both the ambient temperature and the chilling water flow rate have a significant effect on the system. Researchers should focus more on the overall performance of the system rather than a specific parameter or a single component. Abstract: A phase change material (PCM) based solar-assisted air source heat pump (PCM-SAHP) system consisting of an air source heat pump (ASHP), PCM unit and solar thermal collector is proposed. The purpose of the system is to enhance the performance of the ASHPs at low ambient temperatures, and to eliminate the discrepancy between the demand and supply side of cooling/heating energy. The paper is organized as follows: In the first section, the design of the system is compared against other analogue systems. Then, an experimental study on the PCM-SAHP system is provided. The improvements to the system are observed for both the cooling and heating modes. The experimental findings indicate that in the cooling mode the ambient temperature still has a significant effect on the operating performance of the system. In contrast, it is found that the effect of the chilling water flow rate (through the PCM unit) on the system performance is relatively subtle. The authors use an equivalent coefficient to analyze the heat transfer status in the PCM unit. The results of the experiment suggest that researchers should focus more on the overall performance of the system rather than on the heat transfer coefficient of a single component.